Prehospital Detection of Life-Threatening Intracranial Pathology: An Unmet Need for Severe TBI in Austere, Rural, and Remote Areas - Whiting, Mark D.; Dengler, Bradley A.; Rodriguez, Carissa L.; Blodgett, David; Cohen, Adam B.; Januszkiewicz, Adolph J.; Rasmussen, Todd E.; Brody, David L. (Frontiers in Neurology, 2020)
Severe traumatic brain injury (TBI) is a leading cause of death and disability worldwide, especially in low- and middle-income countries, and in austere, rural, and remote settings. The purpose of this Perspective is to challenge the notion that accurate and actionable diagnosis of the most severe brain injuries should be limited to physicians and other highly-trained specialists located at hospitals. Further, we aim to demonstrate that the great opportunity to improve severe TBI care is in the prehospital setting. Here, we discuss potential applications of prehospital diagnostics, including ultrasound and near-infrared spectroscopy (NIRS) for detection of life-threatening subdural and epidural hemorrhage, as well as monitoring of cerebral hemodynamics following severe TBI. Ultrasound-based methods for assessment of cerebrovascular hemodynamics, vasospasm, and intracranial pressure have substantial promise, but have been mainly used in hospital settings; substantial development will be required for prehospital optimization. Compared to ultrasound, NIRS is better suited to assess certain aspects of intracranial pathology and has a smaller form factor. Thus, NIRS is potentially closer to becoming a reliable method for noninvasive intracranial assessment and cerebral monitoring in the prehospital setting. While one current continuous wave NIRS-based device has been FDA-approved for detection of subdural and epidural hemorrhage, NIRS methods using frequency domain technology have greater potential to improve diagnosis and monitoring in the prehospital setting. In addition to better technology, advances in large animal models, provider training, and implementation science represent opportunities to accelerate progress in prehospital care for severe TBI in austere, rural, and remote areas.